PENGGUNAAN MEDIA KOMUNIKASI DALAM SOSIALISASI PROGRAM URBAN FARMING DI KOTA SURABAYA - Henny Sri Mulyani; Herlina Agustin (Jurusan Ilmu Komunkasi FISIP Universitas Jenderal Soedirman, 2018)
Communication media is a source of power, a control tool that can be utilized as a substitute for poweror other resources, besides the media is a vehicle that plays a role to socialize the events of communitylife both individually and collectively. To provide food availability independently and sustainably itneeds a breakthrough program through the concept of gardening in the yard of the house or the use ofempty land for planting productive crops. The purpose of research to find out how the background ofmedia usage, type of media used and the form of presentation of messages used in the socialization ofurban farming program in the city of Surabaya. The research method used is descriptive qualitativewith data collection interview, observation and literature study. The results showed that the delivery ofagricultural messages in urban areas from the Surabaya City Agriculture Office to poor families(Gakin) scattered in 31 sub-districts did not use mass media on the grounds that the gakin communityrarely mengengan radio, see television and read the print media so generally the delivery of directmessages done facilitator in this case PPL to poor community society by direct way of technicalguidance in the form of group. Media used more to media antarpersona communication. Messagedelivered on how to do urban farming activities for vegetables with a short harvest period ofapproximately one month, the use of narrow land in the yard so as to support household-scale foodsecurity and add green or green open space.